#TITLE_ALTERNATIVE# - MARSTIGA YUNIAR (NIM 122 02 008), DHANIE
Since the very beginning of its operations in 1983, re-injection process has been executed at the vapor dominated Kamojang geothermal field which was the first geothermal field in Indonesia, to maintain its reservoir pressure. Tracer test has been conducted for the second time in 1992 on KMJ-15 re-injection well to predict the effect of re-injection on temperature decline at production wells and monitoring of the test has been conducted at seven production wells. The multi fracture model which is identical to the uniform porous model is validated using the test data. Cooling predictions with 20 years of production time was conducted after obtaining a good match between the model and the data. Analysis shows that the re-injection flow rate of 15 kg/s results in a relatively small decline of temperature, 0,4-1,4 C per year, which allows the re-injection process to continue.